An 11‐country study to benchmark the implementation of recommended nutrition policies by national governments using the Healthy Food Environment Policy Index, 2015‐2018. (4th January 2019) - Vandevijvere, Stefanie; Barquera, Simon; Caceres, Gabriela; Corvalan, Camila; Karupaiah, Tilakavati; Kroker‐Lobos, Maria Fernanda; L'Abbé, Mary; Ng, See Hoe; Phulkerd, Sirinya; Ramirez‐Zea, Manuel; Rebello, Salome A.; Reyes, Marcela; et al.
Summary: The Healthy Food Environment Policy Index (Food‐EPI) aims to assess the extent of implementation of recommended food environment policies by governments compared with international best practices and prioritize actions to fill implementation gaps. The Food‐EPI was applied in 11 countries across six regions (2015‐2018). National public health nutrition panels ( n = 11‐101 experts) rated the extent of implementation of 47 policy and infrastructure support good practice indicators by their government(s) against best practices, using an evidence document verified by government officials. Experts identified and prioritized actions to address implementation gaps. The proportion of indicators at "very low if any, " "low, " "medium, " and "high" implementation, overall Food‐EPI scores, and priority action areas were compared across countries. Inter‐rater reliability was good (GwetAC2 = 0.6‐0.8). Chile had the highest proportion of policies (13%) rated at "high" implementation, while Guatemala had the highest proportion of policies (83%) rated at "very low if any" implementation. The overall Food‐EPI score was "medium" for Australia, England, Chile, and Singapore, while "very low if any" for Guatemala. Policy areas most frequently prioritized included taxes on unhealthy foods, restricting unhealthy food promotion and front‐of‐pack labelling. The Food‐EPI was found to be a robust tool and process to benchmark governments' progress to create healthy food environments.